Correlation of grade of pulmonary artery pressure with six minutes walk distance and dyspnoea grading in group 3 pulmonary artery hypertension - Shanmuganathan, Aruna; G., Advita; N., Meenakshi; R., Ragulan; Ganga, Nisha; K., Pukazhenthi (International Journal of Advances in Medicine, 2018)
Background: Pulmonary Artery Hypertension (PAH) is defined as mean pulmonary artery pressure greater than 25 mmHg at rest as assessed by Right heart catheterization. 1 PAH secondary to lung disease is categorized under Group 3 PAH according to WHO classification, the major causes being COPD, ILD, OSA etc. Only few studies have analyzed the clinico-radiological profile, severity, morbidity and mortality associated with group 3 PAH. Hence this study was undertaken to study the clinic-radiological and functional profile of patients with group 3 pulmonary hypertension and to correlate grade of PAH with six-minute walk distance (6MWD) and Dyspnoea grading by modified Medical Research Council (mMRC). Primary objective was to correlate grade of PAH with 6MWD and dyspnoea grading (mMRC) in group 3 pulmonary artery hypertension. Secondary objective was to study the clinic- radiological and functional profile of patients with group 3 pulmonary hypertension in a tertiary care centre. Methods: Seventy two patients diagnosed to have PAH by 2D ECHO with underlying lung disease were retrospectively analyzed in Department of Respiratory Medicine, Chettinad Hospital and Research Institute, Chennai. Their demographic data, clinical history, examination, Dyspnoea according to MMRC grading, Chest X ray, CT chest, ECG, 2D ECHO (using VIVID 5), PFT (Easy on PC 2700-1-01. EOPC SN 219295, ATS guidelines), six minute walk test (ATS guidelines) and other Special investigations like CT Pulmonary Angiogram, Polysomnography were included wherever necessary. Results: Out of the 72 patients with group 3 PAH 44.4% belong to the age group of 46-65 years with a mean age of 57.59±13.6 years along with a slight male preponderance. The commonest cause being COPD (27.7%) followed by ILD (15.30%) and Bronchiectasis (5.50%) and the combined etiology contributing to 48.8%. There was a statistically significant positive correlation between grade of PAH and mMRC score (p< 0.05) and significant negative correlation between grade of PAH with 6MWD and FEV1 (p <0.05). Conclusions: This study shows that Simple bed side tools like 6MWD and mMRC score can be used for the evaluation of presence and severity of Group 3 PAH.